2005
DOI: 10.4315/0362-028x-68.10.2123
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of a Novel Multiplex PCR Assay and Detection of Toxigenic Strains of the Species in the Bacillus cereus Group

Abstract: Five different enterotoxins and one emetic toxin of Bacillus cereus have been characterized. To amplify all of the enterotoxin and emetic-specific sequences of the species in the B. cereus group, a multiplex PCR with 12 primer pairs was established. In developing the assay method, a common terminal sequence at the 3' ends of all primers was chosen and a hot start Taq polymerase was used to overcome primer dimer formation. The assay was successfully applied to analyze the toxigenic potential of 162 food-poisoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 27 publications
5
45
1
Order By: Relevance
“…The results showed that 30% (6/20) of B. cereus isolates contained three enterotoxic HBL complex encoding genes hblA, hblC and hblD, whereas 70% (14/20) had no hbl genes. All three enterotoxic NHE complex encoding genes nheA, nheB and nheC were detected in 40% of isolates (8/20), whereas two nhe genes (nheA and nheB) were found in 45% (9/20) of the isolates [39] hblD F hblD R AGGTCAACAGGCAACGATTC CGAGAGTCCACCAACAACAG 205 [39] hblA F hblA R ATTAATACAGGGGATGGAGAAACTT TGATCCTAATACTTCTTCTAGACGCTT 237 [40] nheA F nheA R GAGGGGCAAACAGAAGTGAA TGCGAACTTTTGATGATTCG 186 [39] nheB F nheB R CCGCTTCTGCAAAATCAAAT TGCGCAGTTGTAACTTGTCC 281 [39] nheC F nheC R ACATCCTTTTGCAGCAGAAC CCACCAGCAATGACCATATC 618 [41] cytK1 F cytK1 R AACAGATATCGGTCAAAATGC CGTGCATCTGTTTCATGAGG 623 [42] and one nhe gene (two nheA and one nheB) was found in 15% (3/20) of the isolates. The ctyK1 gene was not detected in any sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that 30% (6/20) of B. cereus isolates contained three enterotoxic HBL complex encoding genes hblA, hblC and hblD, whereas 70% (14/20) had no hbl genes. All three enterotoxic NHE complex encoding genes nheA, nheB and nheC were detected in 40% of isolates (8/20), whereas two nhe genes (nheA and nheB) were found in 45% (9/20) of the isolates [39] hblD F hblD R AGGTCAACAGGCAACGATTC CGAGAGTCCACCAACAACAG 205 [39] hblA F hblA R ATTAATACAGGGGATGGAGAAACTT TGATCCTAATACTTCTTCTAGACGCTT 237 [40] nheA F nheA R GAGGGGCAAACAGAAGTGAA TGCGAACTTTTGATGATTCG 186 [39] nheB F nheB R CCGCTTCTGCAAAATCAAAT TGCGCAGTTGTAACTTGTCC 281 [39] nheC F nheC R ACATCCTTTTGCAGCAGAAC CCACCAGCAATGACCATATC 618 [41] cytK1 F cytK1 R AACAGATATCGGTCAAAATGC CGTGCATCTGTTTCATGAGG 623 [42] and one nhe gene (two nheA and one nheB) was found in 15% (3/20) of the isolates. The ctyK1 gene was not detected in any sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Primer sequences used for the detection of the various genes were specifi ed in the work of Yang et al (2005) - Table II. Two primer pairs were used to detect the same region of the cytK gene, for there was variation in the sequences (cytK1 and cytK2) of the region among diff erent strains.…”
Section: Primer Sequences and Multiplex Pcrmentioning
confidence: 99%
“…The diarrhoeal type enterotoxin is formed by heat-labile proteins which can be inactivated by heat treatment at 56 °C for 5-30 min (Murray et al, 1999). Bacillus cereus produces the following diff erent diarrhoeal ente ro to xins: protein complex (haemolytic HBL and non-haemolytic NHE enterotoxins), enterotoxic proteins (enterotoxin T), cytotoxin K and enterotoxin FM (Yang et al, 2005;Lindbäck et al, 2004). Sergeev et al (2006) classifi ed enterotoxin FM as a haemolytic enterotoxin and as cytotoxin.…”
mentioning
confidence: 99%
See 2 more Smart Citations